Temperature Controls Crystalline Iron Oxide Utilization by Microbial Communities in Methanic Ferruginous Marine Sediment Incubations - Aromokeye, David A.; Richter-Heitmann, Tim; Oni, Oluwatobi E.; Kulkarni, Ajinkya; Yin, Xiuran; Kasten, Sabine; Friedrich, Michael W. (Frontiers in Microbiology, 2018)
Microorganisms can use crystalline iron minerals for iron reduction linked to organic matter degradation or as conduits for direct interspecies electron transfer (mDIET) to syntrophic partners, e.g., methanogens. The environmental conditions that lead either to reduction or conduit use are so far unknown. We investigated microbial community shifts and interactions with crystalline iron minerals (hematite and magnetite) in methanic ferruginous marine sediment incubations during organic matter (glucose) degradation at varying temperatures. Iron reduction rates increased with decreasing temperature from 30 °C to 4 °C. Both hematite and magnetite facilitated iron reduction at 4 ºC, demonstrating that microorganisms in the methanic zone of marine sediments can reduce crystalline iron oxides under psychrophilic conditions. Methanogenesis occurred, however at higher rates with increasing temperature. At 30 ºC, both hematite and magnetite accelerated methanogenesis onset and maximum process rates. At lower temperatures (10 ºC and 4 ºC), hematite could still facilitate methanogenesis but magnetite served more as an electron acceptor for iron reduction than as a conduit. Different temperatures selected for different key microorganisms: at 30 ºC, members of genus Orenia, Halobacteroidaceae, at 10 ºC, Photobacterium and the order Clostridiales, and at 4 ºC Photobacterium and Psychromonas were enriched. Members of the order Desulfuromonadales harbouring known dissimilatory iron reducers were also enriched at all temperatures. Our results show that crystalline iron oxides predominant in some natural environments can facilitate electron transfer between microbial communities at psychrophilic temperatures. Furthermore, temperature has a critical role in determining the pathway of crystalline iron oxide utilization in marine sediment shifting from conduction at 30 °C to predominantly iron reduction at lower temperatures.